Determinant of Continuance Usage Intention of Mobile Payment Application Using Extended Tam Model - Glenward Prasetyo Alomau; Jeanne Ellyawati (Conference Series, 2020)
The purpose of this study is to examine factors that influence on continuance usage intention (CUI) of OVO mobile payment applications in Indonesia. This study uses the concept of the Technology Acceptance Model (TAM) that has been further developed to examine the factors that influence on CUI, namely perceived usefulness (PU), perceived ease of use (PEOU), perceived credibility (PC), social influence (SI), and customer awareness (CA). Some 241 mobile payment application user was recruited as respondents. Data were collected using a cross-sectional survey design with a structured questionnaire via a Google form. SmartPLS is used to verify hypotheses. The study results showed that all observed variables influence positively on CUI of mobile payment application. The study found that the service provider needs to maintain and monitor the functions of PU, PEOU, PC, SI, and CA so that mobile payment application will always be attractive to users to continue using mobile payment application.